2018
DOI: 10.1155/2018/6181432
|View full text |Cite
|
Sign up to set email alerts
|

AICAR-Induced AMPK Activation Inhibits the Noncanonical NF-κB Pathway to Attenuate Liver Injury and Fibrosis in BDL Rats

Abstract: Background To evaluate the AMP-activated protein kinase- (AMPK-) mediated signaling and NF-κB-related inflammatory pathways that contribute to cholestatic diseases in the bile duct ligation (BDL) rat model of chronic cholestasis and verify the protective role of 5-Aminoimidazole-4-carboxamide1-β-D-ribofuranoside (AICAR) against hepatic injury and fibrosis triggered by cholestasis-related inflammation. Methods Animals were randomly divided into three groups: sham-operated group, BDL group, and BDL+ AICAR group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Another important point is that TGF‐β is considered as the key promoting factor in liver fibrosis, as celastrol could up‐regulate SIRT3, whether there is a regulatory role between SIRT3 and TGF‐β? Previous study showed that SIRT3 could deacetylate and activate glycogen synthase kinase 3β (GSK‐3β) to positively regulate its activity, which phosphorylated β‐catenin and Smad to block TGF‐β1 signalling and suppress tissue fibrosis . Therefore, in the future study, the effect of celastrol on GSK‐3β, phosphorylation of β‐catenin and Smad will be investigated to clarify the regulatory role between SIRT3 and TGF‐β.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another important point is that TGF‐β is considered as the key promoting factor in liver fibrosis, as celastrol could up‐regulate SIRT3, whether there is a regulatory role between SIRT3 and TGF‐β? Previous study showed that SIRT3 could deacetylate and activate glycogen synthase kinase 3β (GSK‐3β) to positively regulate its activity, which phosphorylated β‐catenin and Smad to block TGF‐β1 signalling and suppress tissue fibrosis . Therefore, in the future study, the effect of celastrol on GSK‐3β, phosphorylation of β‐catenin and Smad will be investigated to clarify the regulatory role between SIRT3 and TGF‐β.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK is involved in the development of many disease models including liver fibrosis and activation of AMPK inhibited NF‐κB signalling to alleviate liver inflammation and fibrosis . Liver fibrosis can also be ameliorated by AMPK phosphorylation and blockade of mTOR‐dependent cascades .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, pharmacological activation of AMPK has been demonstrated to inhibit TGFβ-induced intracellular lipid droplets depletion and activation of LX2 cells [ 103 ]. Moreover, AMPK activation has also been shown to attenuate liver injury and fibrosis in BDL rats through non-canonical NF-κB pathway inhibition and subsequent downregulation of inflammatory cytokines such as Tnf-α , Il-β , Il-21 , and Ccl21 [ 104 ]. However, a recent study suggested that TWEAK-induced SIRT1 upregulation inhibits LX2 cells senescence in parallel with α-SMA increased expression [ 105 ].…”
Section: Acetylation/deacetylation Of Histones In Liver Fibrosismentioning
confidence: 99%